2015
DOI: 10.1111/apt.13412
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the risk of major gastrointestinal bleeding with non‐vitamin K antagonist oral anticoagulants

Abstract: Summary Background Gastrointestinal (GI) bleeding is a common complication among anticoagulated patients. Non‐vitamin K antagonist oral anticoagulants (NOACs) are associated with increased risk of GI (major and clinically relevant non‐major) bleeding. However, more information is needed regarding severe events. Aim To evaluate the risk of NOACs major GI bleeding. Methods We searched for phase III randomised clinical trials (RCT) evaluating NOACs (apixaban, dabigatran, edoxaban and rivaroxaban) and reporting ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 63 publications
0
38
2
7
Order By: Relevance
“…Notably, among the included studies, the outcome was specifically defined as major GIB in Graham et al , while Chan et al stratified the outcomes and reported the results of minor and major GIB separately. It was reported in the meta‐analysis of RCTs that dabigatran and rivaroxaban were associated with an approximately 50% increase in overall GIB risk compared with warfarin ; however, they were not associated with the risk of major GIB . Thus, the lower risk of GIB observed in the present meta‐analysis may also be partially attributed to the effect of combining overall GIB and major GIB in the outcome.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Notably, among the included studies, the outcome was specifically defined as major GIB in Graham et al , while Chan et al stratified the outcomes and reported the results of minor and major GIB separately. It was reported in the meta‐analysis of RCTs that dabigatran and rivaroxaban were associated with an approximately 50% increase in overall GIB risk compared with warfarin ; however, they were not associated with the risk of major GIB . Thus, the lower risk of GIB observed in the present meta‐analysis may also be partially attributed to the effect of combining overall GIB and major GIB in the outcome.…”
Section: Discussionmentioning
confidence: 43%
“…By contrast, findings from four recent meta‐analyses did not support an association between NOACs and GIB, and did not report separate risks for specific NOACs. Additionally, a recent meta‐analysis by Caldeira et al , which included the most recent RCTs, reported that NOACs were not associated with a risk of major GIB.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of GIB was also increased with high-dose edoxaban of 60 mg daily (HR 1.23), but was reduced with low-dose edoxaban of 30 mg daily (HR 0.89)[14]. However, subsequent systematic reviews and meta-analyses which included more trials with different inclusion and exclusion criteria yielded conflicting results, showing either no or only a marginal increase in the risk of GIB[23-29]. …”
Section: Risk Of Noac-related Gib In Rctsmentioning
confidence: 99%
“…Thus, in a pooled analysis of the phase 3 VTE treatment trials, there was a non-significant trend for less bleeding with the DOACs than with VKAs (RR 0.77, 95% CI 0.49–1.21; p=0.11) 30 .…”
Section: Choosing Amongst the Doacsmentioning
confidence: 94%